A Turning Point for the Service Sector in Thailand - Pracha Koonnathamdee (Asian Development Bank (ADB), 2013)
Although Thailand's service sector accounts for almost half of the national income and has a major stake in national employment, its contribution to the growth of the gross domestic product (GDP) fluctuates. Moreover, the share of the service sector in GDP is decreasing while many developed countries maintain a positive association between the shares of the sector in output and per capita income. This paper investigates this relationship by examining the gross provincial product of 76 provinces to test the hypothesis that the service sector is a growth engine in the Thai economy. Using the fixed-effects model, the estimates confirm two waves of growth. Total factor productivity and revealed comparative advantages are discussed to determine significant service activities. Wholesale and retail trade, tourism and travel-related activities, transportation, and construction all play major roles in contributing to Thailand's economic growth. The government should continue to promote these services with unambiguous policies suitable for each region and province. Educational services also require more attention from pertinent agencies.
hdl:11540/2315
Keywords: O14; O17; R11; 330; service sector; economic growth; structural change; Thai economy; economic development